The Effect of Mouth Breathing on Facial Anthropometry - Hasansulama, Wijana; Boesoirie, Shinta Fitri; Septiani, Fitri (Archives of Plastic Surgery, 2025)
Breathing can occur either through the nose or mouth. Mouth breathing is the process of breathing through the mouth alone or mostly through the mouth for more than 6 months. Mouth breathing can affect facial development. This study aims to look at the effect of mouth breathing on facial anthropometry.This study used a case–control design conducted during March to September 2024 at Dr. Hasan Sadikin Hospital, Bandung, on subjects aged 7 to 23 years who were divided into two groups, namely mouth breathing and nasal breathing. Data were obtained from filling out the MBD-MBS (Mouth Breathing in Daytime and Mouth Breathing during Sleep) questionnaire, taking lateral cephalometric photographs, and cephalometric measurements using the WebCeph application. Statistical analysis was performed with SPSS software using the chi-square and Mann–Whitney tests.There were significant differences in angular parameters between the two groups, namely the Sella-Nasion to Gonion-Gnathion (SN.GoGn) angle (p = 0.029), the Frankfort mandibular angle (FMA; p = 0.023), and the mandibular plane to palatal plane (MP.PP) angle (p = 0.012); the Articulare-Gonion-Menton (ArGoMe) angle was greater in the oral breathing group (p = 0.003). The linear parameter values in both groups were not different (p > 0.05).Mouth breathing affects facial anthropometry, resulting in an increase in retrognathic mandibular and maxillary angles.
Keywords: mouth breathing; cephalometry; mandibular angle; retrognathic